Quantitatively Estimating Carbon Sequestration Potential in Soil and Large Wood in the Context of River Restoration - Hinshaw, Sarah; Wohl, Ellen (Frontiers in Earth Science, 2021)
Restoration aimed at rewetting the valley floor has the potential to increase organic carbon stock in the form of floodplain soil carbon, downed wood, and riparian vegetation. The primary goal of stream restoration is typically to restore habitat or maintain balance between natural ecosystem function and human land use. Although many benefits result from stream restoration, the carbon sequestration potential of different restoration approaches in diverse geographic settings has not yet been quantified. We investigate the carbon storage potential of restored stream segments (known as treatment segments) relative to otherwise analogous degraded and reference segments. We develop a conceptual framework to identify the conditions that maximize carbon storage in relation to characteristics of the river corridor and specific restoration practices and propose response surfaces for carbon storage. We illustrate application and quantification of the conceptual framework using data from a pilot study of treatment, degraded, and reference stream segments along two streams in Oregon, USA. The conceptual model is designed to help managers identify levels of hydrologic connectivity, channel and floodplain dynamics, floodplain vegetation, and other variables that may optimize carbon storage at a treatment site.